Experimental Analysis and Modeling of an Impact Response Along Sets of Steel Sheets Joined with Rivets - Víctor Martínez-Calzada; Felipe de Jesús Tapia-Pérez; Adriana Rodríguez-Torres; Alonso Saldaña-Heredia (Designs)
This paper is focused on understanding how a wave was transmitted along arrays joined with rivets. The arrays were made of steel plates, and each section was joined to the other with five rivets. A total of three arrays were studied, which were compounded by one, two and three steel plates. To determine the wave transmission, a laser, a lens and a camera were set up in the experiment to calculate the in-plane motion both while the structure was still and during the indirect collisions. Results were studied by means of the general theory of elasticity coupled with spectral analysis from a general mathematical model; the latter fitted all the responses with a mean of 98% accuracy.